ANALISIS SIKAP DAN MINAT BELAJAR SISWA KELAS XI IPA DI SMA NEGRI 15 SEMARANG TERHADAP MATA PELAJARAN KIMIA - Aisyiyah Dinnur Utami; Eny Winaryati (Universitas Muhammadiyah Semarang, 2018)
The purpose of this research is to know the measures and the behaviour of students and the lack of interest in of students to study a class of XI at the senior high school 15 Semarang the capital city of against learning to promote disorder to chemical .Was used in the study a method of descriptive of quantitative .The collection of data in the manner of a triangulation of pt pgn promised to supply kuisoner , observation , and conducting interviews .The research sample over the withdrawal of funds there were a total of 57 respondents in the present study.The findings of this glory if it is found of the study are: 1 ) an attitude and activity of student of class XI at the senior high school 15 semarang the capital city of against learning to promote disorder to chemical, 2 ) the activity itself to of students to study in also had an impact indirect positive impact on the lack of interest in of students to study a class of XI at the senior high school n 15 semarang the capital city of against learning to promote disorder to chemical.Keyword :Research, students attitude, interest students, chemical.